Region-specific mitophagy in nucleus pulposus, annulus fibrosus, and cartilage endplate of intervertebral disc degeneration: mechanisms and therapeutic strategies - Feng, Chaoqun; Hu, Ziang; Zhao, Min; Leng, Chuan; Li, Guangye; Yang, Fei; Fan, Xiaohong (Frontiers in pharmacology, 2025)
Intervertebral disc degeneration (IVDD) is a prevalent condition contributing to various spinal disorders, posing a significant global health burden. Mitophagy plays a crucial role in maintaining mitochondrial quantity and quality and is closely associated with the onset and progression of IVDD. Well-documented region-specific mitophagy mechanisms in IVDD are guiding the development of therapeutic strategies. In the nucleus pulposus (NP), impaired mitochondria lead to apoptosis, oxidative stress, senescence, extracellular matrix degradation and synthesis, excessive autophagy, inflammation, mitochondrial instability, and pyroptosis, with key regulatory targets including AMPK, PGC-1α, SIRT1, SIRT3, Progerin, p65, Mfn2, FOXO3, NDUFA4L2, SLC39A7, ITGα5/β1, Nrf2, and NLRP3 inflammasome. In the annulus fibrosus (AF), mitochondrial damage induces apoptosis and oxidative stress mediated by PGC-1α, while in the cartilage endplate (CEP), mitochondrial dysfunction similarly triggers apoptosis and oxidative stress. These mechanistic insights highlight therapeutic strategies such as activating Parkin-dependent and Ub-independent mitophagy pathways for NP, enhancing Parkin-dependent mitophagy for AF, and targeting Parkin-mediated mitophagy for CEP. These strategies include the use of natural ingredients, hormonal modulation, gene editing technologies, targeted compounds, and manipulation of related proteins. This review summarizes the mechanisms of mitophagy in different regions of the intervertebral disc and highlights therapeutic approaches using mitophagy modulators to ameliorate IVDD. It discusses the complex mechanisms of mitophagy and underscores its potential as a therapeutic target. The objective is to provide valuable insights and a scientific basis for the development of mitochondrial-targeted drugs for anti-IVDD.